On The Analytical Solutions of Nonhomogeneous Heat equations (Journal of the College of Basic Education, 2022)
In this paper, we consider the analytical solution of the Nonhomogeneous mixed problem of the Heat equation. Namely, we use the separation of variables and Duhamel’s principle to derive the formula of the general solution to this problem. Moreover, we find the solution for a special case of this problem as an application to our result